Audit Kas dalam Perspektif Manajemen Risiko: Analisis Faktor Fraud dan Human Error pada Entitas Bisnis di Indonesia - Darmi Patulak; Haspina; Deswita Nuraidha S; Harun Al Rasyid; Fina Ruzika Zaimar (STKIP Subang, 2025)
This study aims to analyze cash audits from a risk management perspective by highlighting fraud and human error factors within business entities in Indonesia. Cash is the most liquid asset and the most vulnerable to misuse, thus requiring a strong internal control system to ensure the reliability of financial reporting. This research employs a literature review by gathering relevant previous studies related to cash audits, risk management, fraud, and human error. The findings show that fraud risks often arise due to weak segregation of duties, inadequate supervision, and the continued use of manual recording systems. Meanwhile, human error is triggered by limited understanding of procedures, high workloads, and insufficient competency in using accounting technology. Risk-based cash audits supported by regular reconciliations, layered authorization, and digital systems are proven effective in minimizing cash irregularities. In addition, surprise audits and whistleblowing systems strengthen early detection of fraud. This study concludes that integrating risk management, improving human resource competence, and modernizing audit systems are key to preventing fraud and human error, while enhancing the financial integrity of business entities.